Implementasi Kompensasi, Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening - Kurniawan, Deri Alan; Gumilar, Irfan Rizki; Rahmat, Nurul Alifah (Universitas Bunda Mulia, 2023)
The main issue in employee performance at leather tanning Small and Medium Enterprises (SMEs), Garut Regency is when employees feel a lack of specific attention that allows the company to innovate and progress. This difficulty leads to challenges in various aspects, such as providing adequate compensation in accordance with government regulations, dealing with an organizational culture that tends to resist change, and operating in a less supportive work environment that hinders collective progress among supervisors and colleagues. Consequently, this impacts both employee satisfaction and performance. The study population consisted of 981 employees of leather tanning SMEs. The research findings indicate that compensation indirectly has a positive and significant impact on employee productivity through increased job satisfaction among leather tanning SMEs employees in Garut Regency. Organizational culture also indirectly influences employee performance positively and significantly through job satisfaction among the same employees. However, the work environment does not have a significant indirect effect on employee performance through job satisfaction.